2004
DOI: 10.1021/ol049422u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Quaternary Amino Acids Bearing a (2‘Z)-Fluorovinyl α-Branch:  Potential PLP Enzyme Inactivators

Abstract: Protected alpha-formyl amino acids, themselves available from the corresponding alpha-vinyl amino acids, are stereoselectively transformed into the (Z)-configured alpha-(2'-fluoro)vinyl amino acids via a three-step sequence. The route employs McCarthy's reagent, diethyl alpha-fluoro-alpha-(phenylsulfonyl)methyl phosphonate, and proceeds via the intermediate (E)-alpha-fluorovinyl sulfones and (E)-alpha-fluorovinylstannanes. The latter may either be exploited as novel cross-coupling partners for fluorovinyl bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
(30 reference statements)
0
20
0
Order By: Relevance
“…This is notable because radical sulfide-stannane interchange reactions are known to sometimes lead to scrambling of alkene geometry. 58b,59 That said, for α-fluorovinylsulfones, both we 39b and McCarthy 60 have observed that radical vinyl sulfone/stannane proceeds with clean retention of configuration, with examples of both geometric isomers in McCarthy’s case, providing strong experimental evidence for a stereospecific transformation, at least in these cases. In this regard, it is important to note that classic studies showed that simple vinyl stannanes can be isomerized upon heating in the presence of trialkyltin radical.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…This is notable because radical sulfide-stannane interchange reactions are known to sometimes lead to scrambling of alkene geometry. 58b,59 That said, for α-fluorovinylsulfones, both we 39b and McCarthy 60 have observed that radical vinyl sulfone/stannane proceeds with clean retention of configuration, with examples of both geometric isomers in McCarthy’s case, providing strong experimental evidence for a stereospecific transformation, at least in these cases. In this regard, it is important to note that classic studies showed that simple vinyl stannanes can be isomerized upon heating in the presence of trialkyltin radical.…”
Section: Resultsmentioning
confidence: 75%
“…26c As DFMO is utilized to treat African sleeping sickness, 26d and in clinical trials as a chemotherapeutic, 65 this property should not be regarded as limiting the potential utility of this inhibitor in chemical biology or biomedicine. That said, it is somewhat surprising that both enantiomers inactivate LDC here given the quite different behavior with the α-(l′-fluoro)vinyl trigger, 39a for example. Clearly, future investigations are warranted here to understand the mechanistic underpinnings of these different enantiospecifities of inhibition.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations